Pemberdayaan Kader PKK dalam Pengolahan Tanaman Toga di Desa Celuk - Suka Astini Dewa Ayu Agung Alit; Luh Gde Evayanti; Dewa Ayu Putu Ratna Juwita; Sagung Putri Permana Lestari Murdhana Putere; I Wayan Sudiarta; Komang Trisna Sumadewi (Warmadewa Minesterium Medical Journal, 2024)
Processing of toga plants or traditional medicinal plants is an important part of human cultural heritage. Toga plants are rich in active compounds that have pharmacological effects and health benefits. Interest in the use of the toga plant as an alternative treatment is increasing. Toga plant processing involves various stages, from planting to extracting active compounds, with the important role of technology and innovation. The importance of the toga plant processing industry involves economic aspects, biodiversity conservation, and preservation of cultural traditions. The development of this industry requires a holistic approach involving various parties, from farmers to consumers, to ensure sustainability and welfare of the communities involved in this process. The partners in this service are the PKK Cadres of Celuk Sukawati Gianyar Village, totaling 8 people and coordinated by the PKK Cadre Chair. There are problems that have been identified by partners, namely economic and health problems. The economic problem is the decreasing economic capacity of partners, while the health problem is the lack of cadre skills regarding the use of family medicinal plants in health. The solution for partners to these two problems is to provide education regarding the use of toga plants and training regarding processing of toga plants. Partners are given tools and materials to assist partners in processing toga plants. Outcomes include increasing the knowledge of â‰¥ 80% of partner members regarding the use of toga plants and â‰¥ 80% of partner members receiving training in processing toga plants to increase family income.